Effect of Extraction Period on Total Phenolics, Total Flavonoids, and Antioxidant Capacity of Ugandan Camellia sinensis (L) Kuntze, Black Primary Grades and Green Tea - Murokore, Biryomumaisho Justus; California, Peter Vuzi; Wacoo, Alex Paul; Wangalwa, Rapheal; Ajayi, Clement Olusoji; Gumisiriza, Hannington; Masawi, Agnes Nandutu (Journal of Food Quality, 2023)
Introduction: Globally, the consumption and production of tea are on the rise because of its beneficial constituents. Scarce literature exists on the e1ects of extraction periods on the contents of the biologically important and protective phytochemicals such as phenolics, 2avonoids, and antioxidants in locally produced teas in Uganda. Aim: This study determined the e1ects of extraction periods on the aqueous total phenolic content (TPC) of local Camella sinensis, black primary grades and green tea, and their ecological di1erences, their total 2avonoid content (TFC), and antioxidant capacities (AOC). Methods: Samples of local tea were collected from Kigezi, Ankole, and Buganda regions, and those of green tea were purchased from a local supermarket in Uganda. Four- and 40-minute infusions were separately prepared for each sample. Total phenolic and 2avonoid contents were determined using the Folin–Ciocalteu and aluminium chloride methods using garlic acid and quercetin as standards, respectively. Antioxidant content was determined using 2,2-diphenyl-1- picrylhydrazyl (DPPH) free radical scavenging and ferric reducing assay power (FRAP) methods, using ascorbic acid as the standard. Results: Green tea had the highest total phenolic content both with four-minute (9.50 ±0.25 mgGAE/g) and 40-minute (25.81±1.13 mgGAE/g) extractions, followed by D1 (4.14±0.33 mgGAE/g) at four minutes and PF (23.60±2.37 mgGAE/g) at 40 minutes. Regionally, Kigezi (4.71±0.09 and 22.13±0.85 mgGAE/g) at four and 40 minutes, respectively, gave the highest TPC. In TFC, tea from Buganda (4,371±0.00 2gQE/g) was the highest. In DPPH and FRAP, GT (93.82±0.03%, 39.04±0.02AAE2g/mL) was the best, followed by Buganda tea (88.71±0.03%, 36.99 ±0.01AAEμg/mL), respectively. Conclusion: Longer extraction periods increase TPC in all teas. Green tea generates approximately twice the TPC generated by black tea in four-minute infusions. Green tea gives higher TPC, DPPH, and FRAP but less TFC than some black teas and is perhaps the best in terms of protection against oxidative damage to the body.
Keywords: Extraction Period; Total Phenolics; Total Flavonoids; Antioxidant; Black Primary Grades; Green Tea